Elusive Potential: Natural Gas Consumption in the CIS and the Quest for Efficiency - Pirani, S (Oxford Institute for Energy Studies, 2011)
While the former Soviet Union is usually thought of as a gas producing region, it is also the second-largest regional market behind north America – and that even modest changes in consumption could have big implications for future production in the region, the investment required for it and the availability of gas for export markets. The paper considers the substantial demand reduction that could be achieved with efficiency measures, and the reasons why progress towards these has been painfully slow and the potential largely unrealised. The paper concludes that some efficiency gains have already been made, and more could be achieved quite soon, largely as a result of the long-term trend towards higher gas prices, whereas larger-scale gains, dependent e.g. on power and heat sector reforms, will take much longer. The analysis is underpinned by a detailed study of the statistical information available, with particular reference to consumption by various economic sectors.